Pengaruh Karakteristik Perusahaan Terhadap Pengungkapan CSR (Corporate Social Responsibility) pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Nadiah, Nadiah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2012)
ABSTRACT Corporate Social Responsibility (CSR) is the liability of an organization that not only provide goods and services that are good for society, but also maintain the quality of the social environment and physical, and also give contribute to community welfare which they are life. The disclosure of corporate social responsibility become a liability for the company in the form PT by UU Perseroan No. 40 Year 2007 about Perseroan Terbatas, Bab V, Pasal 74. The aim of this research is to test and find the effect of size company, profitability, profile company, size board of commissioners, and leverage toward to disclosure of corporate social responsibility on manufacturing companies. Population of this research is manufacturing comoanies year 2008-2011. This research used judgement sampling techniques and obtained sample of 124 companies. Analysis tool used multiple regression analysis and measurement for disclosure of CSR used GRI indicators. The results show that profile company influence on the disclosure of corporate social responsibility. In contrast, size company, profitability, size board of commissioners, and leverage has not influence toward to disclosure of corporate social responsibility. Key words : size company, profitability, profile company, size board of commissioners, leverage, CSR